The EU-Georgia Association Agreement: An Instrument To Support The Development Of Georgia Or Lip Service? - Kawecka-Wyrzykowska, Elżbieta (Comparative Economic Research. Central and Eastern Europe, 2015)
On 1 September 2014, the Association Agreement (AA) between the EU and Georgia partially came into force. Its main pillar is a “deep and comprehensive free trade agreement” (DCFTA). It provides for the full liberalisation of trade in industrial products and substantial reduction of barriers in agricultural trade. A significant part of the AA is devoted to the elimination of regulatory barriers to trade (e.g. technical standards). The Agreement provides for a progressive and partial liberalisation of trade in services as well as for fast and deep elimination of barriers to capital flows. The liberalisation of the movement of workers is of a very limited scope however. Provisions of the EU–Georgia AA resemble the earlier Europe Agreements (EAs) signed by the Central and Eastern European Countries, albeit there are many differences as well. It is expected that the AA will bring about a number of advantages for Georgia, including: (a) stabilisation of its economic and legal system, thus making it more predictable for investors and more business friendly; (b) alignment of many business laws to those in the EU, which will broaden the market for Georgian products and services; (c) better implementation of business laws. The short term advantages resulting from trade liberalisation will be modest for Georgia, partly because it granted open access to its market before the AA entered into force. Implementation of the Agreement will involve adjustment costs, which are usually an inevitable part of the path to increasing exports to the huge EU market.